Seizures following Intoxication with a Common Antituberculosis Drug - Adnane Lahlou; Saïd Benlamkaddem; Mohamed Adnane Berdai; Mustapha Harandou (Hindawi Limited, 2019)
Isoniazid is an antimycobacterial agent commonly prescribed in most tuberculosis chemotherapy regimens. Its side effects are widely known including mainly liver toxicity and peripheral neuropathy. The toxic effects of isoniazid are dose-related. Toxic doses are estimated at 35-40 mg/kg and fatal doses at 150 mg/kg. Treatment consists primarily of basic life support, antiepileptic drugs, and pyridoxine. The case is of one of the children with intentional isoniazid poisoning, the drug belonging to an uncle currently under antituberculosis treatment, resulting in tonic-clonic seizures. During her hospitalization in the paediatric intensive care unit, her neurological status as well as her lab values was closely monitored, and despite initial deterioration, the patient was discharged from critical care a week after full recovery.